PENGARUH LOKASI DAN HARGA TERHADAP KEPUASAN KONSUMEN PERCETAKAN SIFIKA JAYA MEDAN - Firuman Arta Maslian Halawa; Amirudin Amirudin; Mella Yunita (STIE Mahardhika, 2026)
This study aims to examine and describe whether business location has a significant positive effect on consumer satisfaction at Sifika Jaya Medan, whether pricing has a significant positive effect on consumer satisfaction at Sifika Jaya Medan, and whether business location and pricing simultaneously exert a significant positive effect on consumer satisfaction at Sifika Jaya Medan. Data were collected through a structured questionnaire, and data analysis encompassed validity testing, reliability testing, classical assumption testing, and hypothesis testing using multiple linear regression analysis. The findings indicate that business location partially exerts a significant effect on consumer satisfaction (p-value = 0.000 < 0.05). Similarly, pricing partially demonstrates a significant effect on consumer satisfaction (p-value = 0.000 < 0.05). Furthermore, business location and pricing simultaneously exert a significant effect on consumer satisfaction (p-value = 0.000 < 0.05). It is therefore recommended that the management of Sifika Jaya Printing, Medan, devote greater attention to the factors influencing consumer satisfaction so that the overall level of consumer satisfaction may be further enhanced.